2012
DOI: 10.1371/journal.pntd.0001493
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Changes and Quality of Life in Neurocysticercosis: A Longitudinal Study

Abstract: BackgroundFew studies have focused on the cognitive morbidity of neurocysticercosis (NCC), one of the most common parasitic infections of the central nervous system. We longitudinally assessed the cognitive status and quality of life (QoL) of patients with incident symptomatic NCC cases and matched controls.Methodology/Principal FindingsThe setting of the study was the Sabogal Hospital and Cysticercosis Unit, Department of Transmissible Diseases, National Institute of Neurological Sciences, Lima, Peru. The des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Substantial studies have indicated a correlation between CNS inflammation and cognitive impairment in a number of neurological diseases, e.g., Alzheimer's disease (AD), because CNS inflammation has been confirmed to be implicated in the development of amyloid neuritic plaques, one of the hallmarks of AD (179,180). The impact of T. canis infection on cognitive development in humans is sorely lacking, with very few clinical or populationbased studies having examined the relationship between neuropsychological parameters and T. canis seropositivity (18,181).…”
Section: Cognitive Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial studies have indicated a correlation between CNS inflammation and cognitive impairment in a number of neurological diseases, e.g., Alzheimer's disease (AD), because CNS inflammation has been confirmed to be implicated in the development of amyloid neuritic plaques, one of the hallmarks of AD (179,180). The impact of T. canis infection on cognitive development in humans is sorely lacking, with very few clinical or populationbased studies having examined the relationship between neuropsychological parameters and T. canis seropositivity (18,181).…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…The pathogenesis of dementia is postulated to be very similar to that of cognitive dysfunction (196), indicating that CNS inflammation is implicated in this neurodegenerative disease due to the development of amyloid neuritic plaques (179,180).…”
Section: Dementiamentioning
confidence: 99%
“…Over time (6 month-follow up) people with NCC-based epilepsy, who were all treated with albendazole, had significant improvement in psychomotor speed and working memory, but there were no significant changes in any of the cognitive test scores above, although a general trend for better performance after treatment was visible. Both epilepsy groups were controlled for seizure frequency and antiepileptic medication was kept constant during the study period [102].…”
Section: Staging Pathology and Clinical Characteristics Of Neurocystmentioning
confidence: 99%
“…In Mexico, NCC‐associated severe chronic headaches and epilepsy were recently reported to reduce the quality of life of patients with NCC under care and incur a considerable number of disability adjusted life years (DALYs) . Reduction in the quality of life of patients with NCC has also been reported in Brazil and Peru and substantial numbers of NCC‐associated DALYs have been reported from Nepal and Cameroon .…”
Section: Introductionmentioning
confidence: 99%